Combustion Modeling of a Fixed Bed Downdraft Biomass Gasifier Using Computational Fluid Dynamics Design - Abdulrahman, S. A.; Abdulrahim, A. T.; El-Jummah, A. M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Thermochemical conversion of biomass in a gasifier for the production of syngas provides the enabling technology for efficient biomass resource utilization. Gasification is a complex process involving the interactions of numerous parameters, hence CFD tool is usually utilized to numerically optimize the design and operation of the gasifier reactor for improved performance. The gasification of multiple biomass usually requires a complex set of facilities for experimental set up in order to determine the optimum operating conditions for maximum gas yield. When this is not available, it can pose a bottle-neck to process development and optimization. In this study, the GAMBIT and FLUENT were used to model and simulate the gasifier reactor with emphasis on the combustion and gasification (reduction) zones in order to maximize the thermal output of the combustor by an optimization of biomass fuel types. Model validation was achieved by showing a close agreement between numerical and experimental results within the same configuration, particularly to show the effect of temperature on the gasification of Fixed Bed Downdraft gasifier. The fraction of initial moisture content, air flow rate, temperature of the pyrolysis zone, and chemical composition of the biomass were the required input data for the model to predict the gasification temperature. Computations were carried out for rice husk, saw dust and corn cobs as gasifier fuels, whereby air was used as the oxidizing agent. The porosity and oxidizer velocity were varied between 0.1 – 0.5 and 5 – 15 m/s respectively. The predicted results compared with experimental data showed good agreement. The simulated temperature gradient also indicated that rich fuel combustion zone was greater for rice husk - corn cobs, an indication that improved gasification and pyrolysis were present.